Problem solving - Real, Terry; Terry, Real (Boston, MA : Allyn & Bacon Professional, 2002)
In this tape, Terry Real takes a group of participants through a step-by-step process for solving problems. He teaches them how to define a problem, visualize solutions, identify obstacles, discover resources for help, and make action plans
Moderated by Jon Carlson, Judy Lewis
Keywords: Problem solving, -- Group; Decision making